Evaluating the geomorphic channel response to beaver dam analog installation using unoccupied aerial vehicles. Issue 12 (22nd July 2021) - Davis, Julianne; Lautz, Laura; Kelleher, Christa; Vidon, Philippe; Russoniello, Christopher; Pearce, Casey
Abstract: Beaver dam analogs (BDAs) are a stream restoration technique that is rapidly gaining popularity in the western United States. These low‐cost, stream‐spanning structures, designed after natural beaver dams, are being installed to confer the ecologic, hydrologic, and geomorphic benefits of beaver dams in streams that are often too degraded to provide suitable beaver habitat. BDAs are intended to slow streamflow, reduce the erosive power of the stream, and promote aggradation, making them attractive restoration tools in incised channels. Despite increasing adoption of BDAs, few studies to date have monitored the impacts of BDAs on channel form. Here, we examine the geomorphic changes that occurred within the first year of restoration efforts in Wyoming using high‐resolution visible light orthomosaics and elevation data collected with unoccupied aerial vehicles (UAVs). By leveraging the advantages of rapidly acquired images from UAV surveys with recent advancements in structure‐from‐motion photogrammetry, we constructed centimeter‐scale digital elevation models (DEMs) of the restoration reach and an upstream control reach. Through DEM differencing, we identified areas of enhanced erosion and deposition near the BDAs, suggesting BDA installation initiated a unique geomorphic response in the channel. Both reaches were characterized by net erosion during the first year of restoration efforts. While erosion around the BDAs may seem counter to the long‐term goal of BDA‐induced aggradation, short‐term net erosion is consistent with high precipitation during the study and with theoretical channel evolution models of beaver‐related stream restoration that predict initial channel widening and erosion before net deposition. To better understand the impacts of BDAs on channel morphology and restoration efforts in the western United States, it is imperative that we consistently assess the effects of beaver‐inspired restoration projects across a range of hydrologic and geomorphic settings and that we continue this monitoring in the future. Abstract : We extracted patterns of erosion and deposition around beaver dam analogs (BDAs) using unoccupied aerial vehicles (UAVs). BDAs enhanced both erosion and deposition during the first year after installation relative to an upstream control reach. While enhanced erosion around BDAs may seem counter to desired long‐term restoration outcomes, short‐term net erosion is consistent with the 1 year study duration, physical processes in the watershed, and theoretical channel evolution models.